2022
DOI: 10.3389/fenvs.2022.993973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term application of organic manure and chemical fertilizer on soil properties and microbial communities in the agro-pastoral ecotone of North China

Abstract: Long-term irrational fertilizer inputs affect soil nutrients conditions in the agro-pastoral ecotone of North China. However, the mechanisms by which biotic and abiotic factors are affected by different fertilizer types remain unclear. A 16-year, long-term fertilization experiment was conducted to explore how soil physicochemical properties and microbial communities respond to different fertilizer types at an experimental site in North China. The key environmental factors that drove changes in soil microbial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…The data indicated that the addition of residues helped to increase MBC, which is also considered one of the labile pools of SOC. Our findings conform to the notion that greater organic fractions improve microbial populations and their diversity in the soil, which ultimately increase MBC [69]. In CA practices, greater aeration in the topsoil might have increased the mineralization of SOM and thus increased MBC, nitrogen and microbial population [70].…”
Section: Discussionsupporting
confidence: 88%
“…The data indicated that the addition of residues helped to increase MBC, which is also considered one of the labile pools of SOC. Our findings conform to the notion that greater organic fractions improve microbial populations and their diversity in the soil, which ultimately increase MBC [69]. In CA practices, greater aeration in the topsoil might have increased the mineralization of SOM and thus increased MBC, nitrogen and microbial population [70].…”
Section: Discussionsupporting
confidence: 88%
“…Similar fertilization schemes reduced bacterial diversity and altered the bacterial community composition of northeastern Chinese black soils within two successive crop seasons [10]. These findings emphasize the necessity of the substitution of chemical fertilizers with organic amendments, which in turn cause less environmental degradation and contribute to soil health and quality [11][12][13].…”
Section: Introductionmentioning
confidence: 74%
“…Accordingly, Gao et al [11] found that the long-term (16-year) combined application of manure and chemical fertilizers enhanced soil fertility and provided a healthier ecosystem for microbial diversity/population compared with chemical fertilization alone in the Inner Mongolia Autonomous Region, North China. Du et al [12] also suggested that the partial replacement of chemical fertilizer with manure increased the formation of macro-aggregates, soil carbon storage, and soil productivity in an arid gravel field of Northwest China.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, organic fertilizers have shown to signi cantly impose less environmental pollution and improve soil quality and fertility (e.g., Karažija et al, 2016;Gao et al, 2022;Du et al, 2022). Karažija et al…”
Section: Introductionmentioning
confidence: 99%